Support mechanisms for deterministic MAC in IEEE 802.11p - Cruz, Cristóvão André Antunes (2015)
Transportation systems play an extremely important role in modern society. A huge research e ort has been devoted to this eld in the past few years making them safer cleaner and more e cient, originating the so-called Intelligent Transportation Systems (ITS). While some of the enabling technologies are entering their mature phase, there are still many open problems that must be solved before such systems can be e ectively leveraged. Specifically, the medium access is regarded as being one of the most challenging issues to solve in order to provide dependable wireless communications in vehicular networks [BUSB09]. The standard protocols have been shown to fail in addressing this issue and some possible solutions are being proposed, but despite the di culty of correctly modelling the channel dynamics, most work on MAC protocols for real-time vehicular communications has been performed under simulated environments, using simplistic assumptions that do not necessarily hold in a read environment. The implementation of a deterministic MAC scheme is hampered by the fact that commercial devices do not allow modi cations to the standard MAC mechanism, and the development of a device from scratch to implement one Medium Access Control (MAC) scheme is an extremely laborious endeavour. However, over the last few years, the IT2S platform for vehicular communication has been developed and is now in a stage that allows implementation and testing of new solutions for the vehicular communications environment. It is a exible platform that allows modi cation to be made in any layer of the communication stack and therefore suited to be adapted for the implementation of new MAC schemes. This work presents an overview of MAC mechanisms capable of providing deterministic real-time access and assesses the features a communications device must include in order to allow the implementation of these mechanisms. It then proposes an implementation of such as device based on the existing IT2S plaform. A exible solution was obtained that allows all the studied MAC schemes to be implemented purely in software, with no modi cations required to the hardware mechanisms, lowering the needed amount of skills required to perform a working implementation of a novel MAC scheme. The performance of the solution was also found to be appropriate for the required uses. It is now possible to create test beds for new MAC schemes and perform more concrete and accurate analysis of their performance.